Prawo do zapłodnienia in vitro w Polsce i na świecie - Łowińska, Ewa (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
In vitro fertilization involves many issues that need to be regulated by law. The main one is the status of the embryo and arising from it other concerns such as cryoconservation of embryos, assisted reproductive techniques, gamete donation, surrogacy, or preimplantation diagnosis. This paper surveys the legal regulation of in vitro fertilization at different levels of the law systems, from international standards, through regional regulations, to the national law.